STRATEGIES USED BY SUPPLY CHAIN ACTORS TO STAY IN FRESH TOMATO BUSINESS IN BAUCHI STATE, NIGERIA - Atman, F. M.; Shehu, A.; Yakubu, S.; Bala, A. H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to examine the strategies applied by the supply chain actors to stay in fresh tomato business in Bauchi State, Nigeria. A multistage sampling technique was used to select 301 producers, 105 wholesalers and 252 retailers making a total of 659 Supply Chain Actors (SCA) for the study. The data were analysed using descriptive statistics only. The result shows that 35.67% of the producers used regular customers as a strategy to reduce transportation cost. About 44.68% and 58.78% of wholesalers retailers use collective transportation as means of reducing cost of transportation respectively. The result also indicates that 69.10%, 94.29%, 80.56% and 77.50% of producers, wholesalers, retailers and consumers belong to a cooperative society respectively. Further, a significant proportion (31.75%) of the producers used multiple production as strategy to stay in business. About 25.18% and 25.78% of wholesalers and retailers used collective transportation respectively. Again the result shows that producers (48.94%), wholesalers (35.64%), retailers (38.90%) and consumers (39.6%) sell and purchase their fresh tomato in farm gate, urban market from street hawkers. From the result it can be observed that producers (83.9%), wholesalers (91.4%) and retailers (58.3%) handled between 1 to 900 of fresh tomato per month. The result shows that 35.9% of the producers, 47.6% of wholesalers and 93.7% of the retailers sold their tomato at 601-700, 701-800, 800 and above per baskets respectively. the result also indicates that 17.61% of the tomato was sold by commission agents, 15.73% were sold by rural assemblers and 33.33% were sold to outside Bauchi state wholesalers. It can be concluded that SCA use one form of strategy to reduce cost of transportation and or to stay in business. The study recommend that SCA can contribute through cooperatives and buy bigger vehicles to ease transportation cost.